Exploring the determinants of bee diversity in tropical urban areas and their implications for conservation - Gomes, Ingrid N.; Silva, Victor H.D.; Gonçalves, Rodrigo B.; Ordónez-Parra, Carlos A.; Procópio-Santos, Carolina P.; Queroz, Sebastian O.; Castro, Diego M.P.; Pena, João Carlos [UNESP]; Maruyama, Pietro K. (Elsevier, 2025)
While urbanization is known for its adverse effects on biodiversity and ecosystem functioning, urban vegetation has been shown to support diverse bee communities. Still, the drivers behind such biodiversity remain poorly understood, especially regarding the effects of urbanization on bees’ functional traits and their interactions with plants. Here, we investigated how bees’ taxonomic diversity, functional traits, and their interactions with plants are structured across a tropical urban landscape. We found that generalist bees dominated the landscape, accounting for 79% of all observed interactions. Plant species richness positively influenced bee richness, while bee abundance was positively influenced by plant species richness and negatively by the proportion of native plants. Urbanization predictors affected bee traits, with highly eusocial and above-ground nesting bees declining as plant richness increased, while ground-nesters increased. Generalist bees responded positively to higher proportions of impermeable surfaces, while specialists were negatively affected. Larger bees were more abundant in landscapes with higher diversity of plants. Irrespective of these changes, bee-plant interaction networks were unaffected by urbanization intensity, suggesting some stability for pollination services in these spaces. These findings highlight the complex ways in which specific bee traits are filtered out or benefited in urban communities and emphasize the necessity of considering the link between specific urbanization drivers and functional traits when planning bee-friendly urban landscapes.